FOREIGN EXPERIENCE OF USING LAND RESOURCES IN ECONOMIC SECTORS - Navotova, Dilnoza Ibrogimovna (SCIENCE and SOCIETY, 2026)
This scientific article analyzes the processes of land resource use in economic sectors based on an economic-geographical approach. The study examines the territorial distribution of land resources, natural and economic potential, and their impact on the characteristics of their location in the agricultural, industrial, transport, and service sectors using the experience of different countries. It also reveals the role of territorial differentiation, economic zoning, infrastructure factors, and environmental constraints in the use of land resources. In developed countries, mechanisms for the effective use of land resources through land management, territorial planning, and digital cadastral systems are analyzed.